CLINICAL MANIFESTATION OF CERVICAL NEUROFIBROMA TYPE 1 IN PATIENTS OF A TERTIARY CARE HOSPITAL - Siddiq, Mohammad; Khanzada, Khalid; Rehman, Riaz ur; ul Haq, Mian Iftihar; Shah, Mewat; ., Anayatullah (Journal of Postgraduate Medical Institute, 2012)
Objective: To determine the clinical presentation of cervical neurofibroma type 1 (NF 1)tertiary care hospital. Methodology: This descriptive study was conducted at Neurosurgery department, Lady Reading HospitalPeshawar from February 2001 to July 2011. A total 31 patients with symptomatic cervical spineneurofibromas who underwent surgical decompression and tumor resection were included in this study.Both gender (male and female) and patients in the age range of 20-70 years were included in this study.The patients' demographic details and clinical manifestation were entered into a semi structured proforma.Data was analyzed through statistical program SPSS version 11. Results: Out of 31 patients, there were 17(54.8%) males and 14(45.2%) females. The age of patientsranged from 20 to 70 years. In this study the overall mean age was 32.38 years. Majority of patientsfifteen (48.38%) were in the age range of 31-40 years. Most common clinical presentation of patient wasquadrapresis in seventeen (54.8%) patients. Conclusions: Cervical neurofibroma type 1 commonly occurred in the third decade of life. quadriparesiswas the common clinical presentation of cervical cord neurofibroma type 1.